Analyzing the disparities in the coverage of maternal and child health services: A district-level cross-sectional analysis of Jammu and Kashmir - Mohd Taqi; Susmita Sarkar; Mohd Mazhar Ali Khan (Wolters Kluwer Medknow Publications, 2020)
Background: Improving overall coverage of maternal and child health (MCH) services is essentially required if India in general and Jammu and Kashmir state in particular have to attain the Sustainable Development Goals by the year 2030. Thus, the disparities in coverage of MCH services need to be assessed and addressed. Objectives: The objective of this study was to examine the variation in coverage rates for a key set of interventions in MCH services and to assess the relationship between coverage gap and socioeconomic development across the districts of Jammu and Kashmir. Methods: Data from the National Family Health Survey-4 (NFHS-4), 2015-2016, Census of India 2011, and Digest of Statistics Jammu and Kashmir were used to construct two composite indexes of coverage gap and socioeconomic development at district level. Cronbach's alpha was used to assess the internal consistency of indicators used in the two indexes. Results: The overall coverage gap in the state was 28.17%, and the size of coverage gap was largest for family planning interventions (55.8%), followed by treatment of sick children (26.95%) and maternal and newborn care (18.75%), and was smallest for immunization (10.5%). There is a moderate negative correlation between coverage gap and socioeconomic development (r = −0.63, P = 0.01). Conclusion: Coverage of MCH services and socioeconomic development has a significant disparity in the districts of Jammu and Kashmir. Resource-rich and more urbanized districts are much ahead of the poor and less urbanized districts in terms of the usage of MCH services.